1999
DOI: 10.1902/jop.1999.70.4.364
|View full text |Cite
|
Sign up to set email alerts
|

Anorganic Bovine Bone Supports Osteoblastic Cell Attachment and Proliferation

Abstract: These results demonstrate that this anorganic bovine bone graft material is able to support the attachment and proliferation of osteoblastic cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0
5

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 18 publications
3
45
0
5
Order By: Relevance
“…34,35 Our findings supplement and extend a recent report on the early (up to 24 h) attachment and proliferation of neonatal rat calvaria cells on the same natural bone mineral (Bio-Oss) in particulate form. 36 We observed the formation and accumulation of mature collagen fibrils. This reflects the complete processing of procollagen to mature collagen ␣-chains, including the formation of two covalent nonreducible crosslinks (HP and LP) which are formed by a sequence of posttranslational modifications.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…34,35 Our findings supplement and extend a recent report on the early (up to 24 h) attachment and proliferation of neonatal rat calvaria cells on the same natural bone mineral (Bio-Oss) in particulate form. 36 We observed the formation and accumulation of mature collagen fibrils. This reflects the complete processing of procollagen to mature collagen ␣-chains, including the formation of two covalent nonreducible crosslinks (HP and LP) which are formed by a sequence of posttranslational modifications.…”
Section: Discussionmentioning
confidence: 89%
“…[26][27][28][29][30][31][32][33][34][35][36] In the present study, we investigated the attachment, proliferation, and matrix synthesis of human osteoblast-like cells onto highly porous natural bone mineral (Bio-Oss) by SEM, TEM, and biochemical analysis. SEM and TEM analysis after 6 weeks revealed that osteoblast-like cells were able to colonize the biomaterial and to synthesize collagen.…”
Section: Discussionmentioning
confidence: 99%
“…poly(P) stimulates bFGF-induced cell proliferation and vascularization, and these effects resulted in a significantly higher BIC in the Poly(P)/IP-CHA group than the IP-CHA group. A bovine-derived anorganic bone matrix such a Bio-Oss ® has been reported superior bone formation and provides scaffold for osteoblasts as an alternative to autologous bone [20][21][22] .…”
Section: Discussionmentioning
confidence: 99%
“…Some of these xenografts further display an architectural organization with interconnected pores and biomechanical resistance similar to those of human bone (Stephan 1999). …”
Section: Introductionmentioning
confidence: 98%